A bit of implicit differentiation never hurt anyone

Calculus Level pending

Use implicit differentiation to find y y'

( 2 x + y ) 4 + 3 x 2 + 3 y 2 = x y + 1 (2x+y)^4+3x^2+3y^2=\frac{x}{y}+1

y = 4 y 2 ( 2 x + y ) 3 + 6 y 3 + x y 8 y 2 ( 2 x + y ) 3 6 x y 2 y'=\frac{4y^2(2x+y)^3+6y^3+x}{y-8y^2(2x+y)^3-6xy^2} y = y 8 y 2 ( 2 x + y ) 3 6 x y 2 4 y 2 ( 2 x + y ) 3 + 6 y 3 + x y'=\frac{y-8y^2(2x+y)^3-6xy^2}{4y^2(2x+y)^3+6y^3+x} y = x ( 2 x + y ) 4 + 3 x 2 + 3 y 2 y'=\frac{x}{(2x+y)^4+3x^2+3y^2} y = y ( ( 2 x + y ) 4 + 3 x 2 + 3 y 2 1 ) y'=y((2x+y)^4+3x^2+3y^2-1)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Gallagher
Feb 1, 2015

( 2 x + y ) 4 + 3 x 2 + 3 y 2 = x y + 1 (2x+y)^4+3x^2+3y^2=\frac{x}{y}+1

4 ( 2 x + y ) 3 ( 2 + y ) + 6 x + 6 y y = y x y y 2 4(2x+y)^3(2+y')+6x+6yy'=\frac{y-xy'}{y^2}

8 ( 2 x + y ) 3 + 4 y ( 2 x + y ) 3 + 6 x + 6 y y = 1 y x y y 2 8(2x+y)^3+4y'(2x+y)^3+6x+6yy'=\frac{1}{y}-\frac{xy'}{y^2}

y ( 4 ( 2 x + y ) 3 + 6 y + x y 2 ) = 1 y 8 ( 2 x + y ) 3 6 x y'(4(2x+y)^3+6y+\frac{x}{y^2})=\frac{1}{y}-8(2x+y)^3-6x

y ( 4 y 2 ( 2 x + y ) 3 + 6 y 3 + x y 2 ) = y 8 y 2 ( 2 x + y ) 3 6 x y 2 y 2 y'(\frac{4y^2(2x+y)^3+6y^3+x}{y^2})=\frac{y-8y^2(2x+y)^3-6xy^2}{y^2}

y = y 8 y 2 ( 2 x + y ) 3 6 x y 2 4 y 2 ( 2 x + y ) 3 + 6 y 3 + x \therefore y'=\frac{y-8y^2(2x+y)^3-6xy^2}{4y^2(2x+y)^3+6y^3+x}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...